Intertidal seaweeds and their multi-life forms - Anjur, Norashikin (Academic Journals, 2013)
Intertidal areas exhibit wide ranges in their extent and environmental conditions and these potentially can result in complex distributional pattern and life styles for many species including seaweeds. A study on seaweeds diversity and life forms was conducted at two intertidal sites in Negeri Sembilan i.e., (1) Teluk Kemang, a rocky outcrops area extending up to 50 m seaward during low tide, with gradual slope with live and dead corals interspersed with sand and (2) Teluk Pelanduk, a stretch of up to 150 m flat beach with mostly mud, sand and little rocks in between. A total of 36 species (16 Chlorophyta, 10 Phaeophyta and 10 Rhodophyta) and 26 species (11 Chlorophyta, 6 Phaeophyta and 9 Rhodophyta) of seaweeds were identified at Teluk Kemang and Teluk Pelanduk, respectively. Jaccard similarity coefficient of 0.442 based on a presence-absence matrix suggests the seaweed composition and diversity varied between the two sites. Both sites possessed their own many specialist species. Variability in environmental conditions e.g., diverse natural substrates or abandoned drift objects (fishing nets and lines, ropes and tyres) introduced by human had caused variation in seaweed composition, diversity and life forms categories. Epilithic (45.71%) seaweed is the most abundant category at Teluk Kemang followed by, epizoic (24.29%), epipelic (12.86%), epiphytic (8.57%) and drift seaweed (8.57%). Seaweed life forms at Teluk Pelanduk are epilithic (38.46%), epipelic (21.15%), epiphytic (17.31%), drift seaweed (13.46%) and epizoic (9.62%). Seaweed species distribution irrespective of sites reflected those that adapt or have adapted to the environmental conditions, particularly in utilizing the availability of the diverse existing natural hard and soft substrates and abandoned drift objects.